Análise do caso do navio Aquarius e os desafios à aplicação do princípio do non-refoulement frente às dificuldades impostas pela governança internacional conflitiva - Guimarães, Gabriel Braga (2019)
Humanity is experiencing a major migratory crisis and one of the most affected regions is the European continent. The central Mediterranean route, which covers most of the Italian coastline, has become one of the main entry routes for migrants - including refugees. Faced with the vulnerability of the maritime borders, a series of security measures related to migratory flows have been adopted, with the main objective of increasing the security of the external borders of the countries, by means of control actions and containment of such flows, however, it has been realized that such actions are weakening the protection of the rights of migrants by the sea. One example of this problem is the case of the vessel Aquarius, which carried out humanitarian rescue in the Mediterranean Sea and on June 10, 2018 was denied entry in the ports of the Italian coast and, as a result, had to drastically redirect their plans so that they could safely land on land. In this context, it is questioned whether the arbitrary refusal to welcome a group of people, without specifically analyzing the status of each person, is in disregard of international norms, especially the principle of Non-refoulement, or whether it is justifiable under the argument of the defense of sovereignty. The general objective of the research is the analysis of the Aquarius ship case, from the point of view of the principle of Non-refoulement, studying how the phenomenon that generated the ship case occurred in the perspective of the development of European migration policies, as well as, which are possible consequences of the event from the perspective of the norms of International Law and how these effects would be applied in view of the difficulties imposed by conflicting international governance. Since the problem has not yet received the appropriate international treatment, the urgency of the proposed research is clear in order to make it possible to reformulate migration policies at the international level. Regarding the method of investigation adopted, the research is developed from the inductive method, being carried out a bibliographical, documentary and jurisprudential analysis. The development of this research is divided into three chapters. In the first chapter, a summary of the European migratory context is made and the role of Italy in the migratory crisis is explained. In the second chapter, from the point of view of the principle of Non-refoulement a study of the circumstances that involved the case of the ship Aquarius is made. In addition, a brief analysis of the perspective of defense of national sovereignty in the context of the migratory crisis is made, in view of the need to respect the norms of International Human Rights Law. In the third chapter, a case-law analysis of a case similar to that of Aquarius is carried out, as well as, the role of conflictive international governance in the migratory crisis is analyzed. The research is completed by means of a survey of all the arguments presented, indicating possible solutions to the problem presented, among which, it is mainly emphasized the adoption of soft law measures, the systematic interpretation of the norms of International Law, as well as encouraging States to comply with the standards already in force. Keywords: Migrants by the sea. Securitization of migratory movements. Migratory Rights. International refugee rights. Conflictive migration governance. Vessel Aquarius.